THE IMPLEMENTATION OF MERDEKA CURRICULUM IN INDONESIAN JUNIOR HIGHSCHOOL CONTEXT: A NARRATIVE INQUIRY STUDY OF AN ENGLISH TEACHER’S JOURNEY - Vena, Nafilla; Wijanuarto, Risky; Adinul, Berlina; Kristiawan, Dana (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study explores the implementation of the Merdeka Curriculum in Indonesian junior high schools through a narrative inquiry into the lived experiences of an English teacher. Using qualitative methods, including in-depth interviews, and classroom observations, the research investigates how the teacher navigates pedagogical shifts demanded by the new curriculum, including project-based learning, differentiated instruction, and digital literacy integration. The findings highlight four interconnected themes: teacher readiness, innovative instructional strategies, systemic and contextual challenges, and the transformation of professional identity. The teacher's story reveals a complex negotiation between curriculum ideals and classroom realities, underscoring the emotional, intellectual, and institutional labor involved in educational reform. Despite facing limited resources, time constraints, and peer resistance, the teacher demonstrates professional agency, reflective practice, and commitment to student-centered learning. The study concludes that successful curriculum reform hinges on empowering teacher voices, providing contextual support, and fostering reflective communities of practice. It advocates for policy design that is informed by practitioners' narratives and grounded in the realities of diverse educational settings.